EFEKTIVITAS MEDIA PUZZLE DALAM PEMBELAJARAN PBL UNTUK MENINGKATKAN LITERASI NUMERASI PADA MATERI PECAHAN SENILAI KELAS V SD - Suci Mulyani; Syafri Ahmad; Salmaini Salmaini (STKIP Subang, 2025)
ABSTRACT The low level of numeracy literacy skills among elementary school students, particularly in the topic of equivalent fractions, remains an issue that affects the achievement of mathematics competencies. This study aims to determine the effectiveness of puzzle media in Problem-Based Learning (PBL) to improve numeracy literacy skills among fifth-grade students of SD Negeri 27 Anak Air. The research employed a quantitative approach using a One-Group Pretest–Posttest design. The instruments used included a numeracy literacy test, student activity observation sheets, and student response questionnaires. The results showed a significant improvement in numeracy literacy skills, indicated by an increase in the average score from the initial to the final condition, as well as a gain score of 0.62, which falls into the medium–high category. Student activity during learning was categorized as good, with an average of 87%, as reflected in increased participation in discussions, puzzle assembly, and problem-solving. In addition, students’ responses to the use of puzzle media were highly positive, with 91% stating that the learning became more engaging and easier to understand. These findings indicate that puzzle media in PBL is effective as an alternative strategy for improving numeracy literacy in the topic of equivalent fractions.